Interactions of Bacterial Proteins with Host Eukaryotic Ubiquitin Pathways - Perrett, Charlotte A.; Lin, David Y.; Zhou, Daoguo (Frontiers in Microbiology, 2011)
Ubiquitination is a post-translational modification in which one or more 76 amino acid polypeptide ubiquitin molecules are covalently linked to the lysine residues of target proteins. Ubiquitination is the main pathway for protein degradation that governs a variety of eukaryotic cellular processes, including the cell cycle, vesicle trafficking, antigen presentation and signal transduction. Not surprisingly, aberrations in the system have been implicated in the pathogenesis of many diseases including inflammatory and neurodegenerative disorders. Recent studies have revealed that viruses and bacterial pathogens exploit the host ubiquitination pathways to gain entry and to aid their survival/replication inside host cells. This review will summarize recent developments in understanding the biochemical and structural mechanisms utilized by bacterial pathogens to interact with the host ubiquitination pathways.